A Review of Nanostructures in Electrowetting-on-dielectric Systems: From Nanostructured Dielectric Layers to Nanofluids - Budlayan, Marco L.; Patricio, Jonathan N.; Arco, Susan D.; Guerrero, Raphael A. (Current Nanoscience, 2024)
The extensive interest in electrowetting-on-dielectric (EWOD) as a key in advancing the efficiency and controllability of fluid-based microelectromechanical and actuator systems has resulted in a deluge of technological research, especially in the area of microfluidics, liquid lenses, and fluid-based lab-on-chips. More recently, the integration of nanostructures into EWOD-driven devices has shown promising improvement in these devices' performance, design, and miniaturization. Due to the exceptional properties, availability, versatility, and tunability of nanostructures, they are being utilized as components of EWOD systems for various applications. Utilization ranges from fabricating nanodimensional dielectric layers to incorporating nanoparticles in fluid droplets. With the current trend in improving the performance and functionality of EWOD-driven devices at low voltage operations, it is timely to revisit the fundamental principle of EWOD phenomena and how it is extended experimentally using nanostructures. In this paper, we present the different nanostructures investigated as dielectric materials in various EWOD experiments focusing on metal oxide and silicon nitride layers. Notes on the structure of these dielectric layers are also presented. Furthermore, various EWOD experiments employing nanofluid droplets are also described. This paper provides a clear picture of nanostructures' diverse impact on the advancement of EWOD technology. The insights presented in this paper may also serve as a guidepost for future exploration and development of the role of nanostructures in EWOD-driven devices.
Keywords: contact angle